Chapter 6 Parental marital dissolution and the intergenerational transmission of homeownership - Hubers, Christa (Taylor & Francis, 2019)
Children of homeowners are more likely to enter homeownership than are children whose parents rent. We investigate whether this association is dependent on parental divorce, focusing on parental assistance as a conduit of intergenerational transmission. Event history analyses of data for England and Wales from the British Household Panel Survey (BHPS) show that the intergenerational transmission of homeownership is stronger for children of divorced parents compared with children of married parents. Such an eff ect may arise from two channels: (1) children of divorced parents are more in need of parental assistance due to socio-economic disadvantages associated with parental divorce; and (2) compared with married parents, divorced homeowning parents (mothers) rely more on housing wealth, rather than fi nancial wealth, for assisting children. Findings support both explanations. Children of divorced parents are furthermore less likely to co-reside. We fi nd limited evidence that when they do, co-residence is less conductive to homeownership compared with children from married parents.